The Effectiveness of Morning Briefing in Building Employee Engagement at Novotel Bandung Hotel - Cantika Raka Permata Putri; Chandra Hendriyani; Fenny Damayanti (The International Journal of Business Review (The Jobs Review), 2022)
Abstract. After the Covid-19 pandemic has changed the order of the tourism business which must prioritize health, cleanliness, and security. Hoteliers such as Hotel Novotel Bandung anticipate changes in tourist trends by implementing Cleanliness, Hygiene, Sanitation, and Environment (CHSE) certification and developing internal service strategies so that hotel occupancy rates can quickly increase again. Teamwork and achieving the vision become management orientation. Therefore, the morning briefing is used as an internal communication medium to continuously monitor service quality and build employee engagement. This study uses descriptive qualitative methods with data collection techniques using observation, interviews, and secondary data. The results of the study show that having a morning briefing before starting work makes internal communication run smoothly and coordination between departments becomes easier and employee engagement is built. The culture of morning briefings must be carried out regularly to maintain the commitment to creating business sustainability for Novotel Hotels.Keyword. employee engagement; morning briefing, employees; occupancy; hotel